Sound absorption properties at high sound frequency of open cell aluminium foam / Mohd Arifhakim Azizan...[et al.] - Azizan, Mohd Arifhakim; Ismail, Muhammad Hussain; Mohd Salleh, Noor Azlina; Natarajan, David Valliyappan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Open-cell aluminium foam is a type of metallic foam that has been industrialised years ago. It has been found that due to its porous characteristic, it is suitable for sound absorption. The porous characteristic of open-cell aluminium foam is closely related to its sound absorption properties. In this research, the open-cell aluminium foam was produced by infiltration casting method and its sound absorption properties were studied. Infiltration casting is a casting method that uses space holder material in the casting mould and later the mould is infiltrated with molten material by vacuuming and gas purging inside the mould. NaCl was used as the space holder material in order to form the porous structure. The size of NaCl grains is in the range between 1mm to 3 mm. The surface structure of the fabricated open-cell aluminium foam was then observed under an optical microscope while its sound absorption properties were determined using impedance tube test, respected to the ASTM E1050 designation to analyse sound absorption coefficient. It was found that at high sound frequency ranging from 800 Hz to 5000 Hz, open-cell aluminium foam produced from infiltration method gave a higher sound absorption for bigger pore open-cell aluminium foam.